JUDO TRAINING PROGRAM WITH MENTAL REHEARSAL ON THROWING SKILLS OF YOUNG ATHLETES - Phandanouvong, Kanyaphet (Academic Journal of Thailand National Sports University, 2022)
The objective of this research was to develop Judo training program by combining mental rehearsal on two skills of Judo throwing which are Morote Seoi Nage and O Goshi. This was done through efficiency comparison during (E1) and after (E2) training and comparison of throwing skill results prior to and after training week 4 and week 8. 20 Lao youth Judo athletes, aged between 14 to 18 years old were selected as a sample group and they were trained two days per week for eight weeks. Judo training program with mental rehearsal in recorded scores of two throwing skills was used as an analysis tool. Statistics used in analyzing data were mean, standard deviation, repeated measure design at the statistical significance level of .05. The research was found that: The results of score analysis of two style of throwing skills during and after training revealed that the E1/E2 efficiency was higher than the determined criteria (80/80) and the results of mean difference test by using t - test of two styles of throwing skills before and after training revealed that the scores were 81/87 and 83/91 respectively. This result indicated that the success of using training program with mental rehearsal after experimenting was higher than that in pre - experiment. The results of the analysis of repetitive variance within the sample, The Morote Seoi Nage throwing skill had a statistical significant difference at the level of .05 and the Ogoshi throwing skill had a statistical significant difference at the level .05. The results of data analysis comparing the two throwing skills of the samples between Week 1 and Week 4, Week 4 and Week 8 and Week 1 and Week 8 revealed that increasing statistical significance was found at level of .05.